Implementasi Akuntansi Pertanggungjawaban Sebagai Alat Penilaian Kinerja Pusat Biaya Pada Rumah Sakit Umum Wilayah Tarutung - Sahala Purba; Rintan Saragih; Mario Putra Pangihutan Sihite (Jurnal Akuntansi, 2022)
Research is very important to identify the implementation of accountability as a tool for evaluating the performance of a hospital, which can be measured through the organizational structure, the budget arrangement of expenditures and the coding of accounts and statement of operating expenses. This research uses qualitative descriptive research using primary information. Where the method of collecting information is tested through questionnaires and interviews. The respondents to this study were the Planning and Training Department and Support Department of Tarutung Regional General Hospital. The results of Tarutung Regional General Hospital Accountability Accountability have been implemented which is reflected in the organizational structure which clearly and unequivocally separates the powers and responsibilities of each accountability center. Budget regulation for hospital expenditure has been implemented but for coding of accounts it has not been implemented in hospitals as can be seen in 2019 and 2020 LKIP (Government Institutions Performance Reports) over a period of time. The performance of expenditure managers is measured and evaluated by comparing budget targets and budget execution. It is not only an evaluation of the performance of the department head, because there are other aspects apart from the implementation of the responsibility, such as: B. Absenteeism and loyalty. Keywords: Bookkeeping and Cost Center Performance Evaluation